2008
DOI: 10.1158/1078-0432.ccr-07-1801
|View full text |Cite
|
Sign up to set email alerts
|

Novel Blood-Based, Five-Gene Biomarker Set for the Detection of Colorectal Cancer

Abstract: Purpose: We applied a unique method to identify genes expressed in whole blood that can serve as biomarkers to detect colorectal cancer (CRC). Experimental Design:Total RNA was isolated from 211blood samples (110 non-CRC,101CRC). Microarray and quantitative real-time PCR were used for biomarker screening and validation, respectively. Results: From a set of 31 RNA samples (16 CRC, 15 controls), we selected 37 genes from analyzed microarray data that differed significantly between CRC samples and controls (P < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 41 publications
(24 reference statements)
3
88
0
5
Order By: Relevance
“…Han et al identified and validated a five-gene combination that could discriminate CRC from non-CRC samples with sensitivity and specificity of 94% and 77% respectively. 8 Two genes of the combination, CDA and BANK1, were also confirmed to be valuable biomarkers for CRC detection in our study. The same group developed a seven-gene, blood-based biomarker signature that could stratify subjects according to their current relative risk to develop a CRC across a broad range in an average-risk population.…”
supporting
confidence: 73%
“…Han et al identified and validated a five-gene combination that could discriminate CRC from non-CRC samples with sensitivity and specificity of 94% and 77% respectively. 8 Two genes of the combination, CDA and BANK1, were also confirmed to be valuable biomarkers for CRC detection in our study. The same group developed a seven-gene, blood-based biomarker signature that could stratify subjects according to their current relative risk to develop a CRC across a broad range in an average-risk population.…”
supporting
confidence: 73%
“…The Bonferroni adjustment for multiple testing was performed using SISA [25] to control for a family-wise error rate of 0.05, for which a significance level was considered as 0.05/42 = 0.00114. The P-values in the tables are reported in scientific notation if too many digits were needed for the evaluation and to address the issue of et al [14] (Model 2: 7 genes) and Han et al [15] (Model 3: 5 genes) and performed the multivariate logistic regression analysis using the pooled 12 public microarray data sets, in addition to external validation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low sensitivities and specificities for these well-known genes are not considered acceptable for the detection of colorectal cancer. Recently, multiple biomarkers were reported for the detection of colorectal cancer that delivered a better sensitivity or specificity [14][15] . In the present study, expression levels of 28 cancerassociated candidate genes from the study of Quyun et al [16] in peripheral blood samples from 111 colorectal cancer patients and 227 non-cancer controls were analyzed using quantitative real time-PCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La recherche de l'expression de gĂšnes dans le sang circulant pouvant servir de biomarqueurs de dĂ©tection du cancer colorectal est en dĂ©veloppement. Une Ă©tude rĂ©cente a validĂ© la recherche d'une signature (ARN circulant de 5 gĂšnes, par microarray et RT-PCR quantitative) dans cette indication avec une sensibilitĂ© de 94 % et une spĂ©cificitĂ© de 77 % [20].…”
Section: Colosopie Virtuelleunclassified